Иммунный потенциал крови у ортопедических больных с циррозом печени при протезировании съемными пластиночными протезами - Лавровская, О.М. (Таврический медико-биологический вестник, 2009)
У хворих цирозом печінки, що користуються пластинковими знімними протезами з

акриловихпластмас, виявлений ефект підсумовувань негативно го впливу базисів

протезів. Використання розробленої нами технології ваку умного насичення

протезів тімогеном дозволило провести модуляцію імуно го дисбалансу у

ортопедичних хворих з цирозом печінки. The effect of adding up of the negative influencing of bases of prosthetic appliances is

exposed at patients with cirrhosis of liver, using prosthetic applian ces from acryl

plastics. The usage of the technology of a vacuum satiation of pros thetic appliances of

thymogene developed by us allowed to conduct modulation of immune misbalance for

orthopaedic patients with the cirrhosis of liver.